PSVI-27 Kidney damage in cows with steatosis. (5th December 2019) - Nikitina, Anastasia; Kovalev, Sergey; Nikitin, Georgiy; Plemyashov, Kirill; Anipchenko, Polina; Stekolnikov, Anatoly; Nechaev, Andrey; Mikhalev, Vitaliy
Abstract: Steatosis is an often detected pathology in cows. Due to hypertension, the load on the urinary system increases, which is accompanied by kidney damage. Often in cows with steatosis, necritis, pyelitis and kidney dystrophy are detected at autopsy. The goal of this study was to determine the characteristic features of kidney damage in cows with steatosis and to identify alterations in blood biochemistry. In 2018, a histological study was carried out on 7 samples of cow liver and kidneys with signs of hepatorenal syndrome (HRS). Observed pathological changes in the liver in the form of fatty degeneration, as well as a decrease in the content of glycogen in hepatocytes were recorded. The livers had a girder structure, moderately full. The sinusoids of the liver and Disse space were moderately dilated. Portal tracts had a typical histological structure; hepatic triads, represented by an interlobular artery, vein, and bile duct, were detected in the stroma. Schiff-iodic acid by MacManus stain showed decrease or absence of glycogen in the samples. The use of the same staining protocol showed positive staining of the reticular fibers of the interstitial kidney tissue. In the kidneys, hyaline droplet epithelium of the tubule, accumulation of hyaline-like substance in the spaces between the capsule and the vascular glomerulus, and development of fibrosing interstitial glomerulonephritis were noted. Biochemical analysis of blood showed normal levels of creatinine (68.5±2.7 μmol/L), and urea (6.6±0.3 mmol/L), and reduced concentration of albumin to 23.2±0.9%. Liver function parameters were elevated: total bilirubin (28.1±1.9 μmol/L), total protein (89.3±3.4 g/L), gamma-glutamyltransferase (131.9±18.0 IU/L). Urine analysis demonstrated proteinuria and hematuria.